2013
DOI: 10.1016/j.neuroimage.2012.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Detecting microstructural properties of white matter based on compartmentalization of magnetic susceptibility

Abstract: The microscopic structure of neuronal tissue is crucial to brain function, with axon diameter, axonal density and myelination directly influencing signal conduction in the white matter. There is increasing evidence that these microstructural properties alter signal in magnetic resonance imaging (MRI) driven by magnetic susceptibility of different compartments (e.g., myelin sheaths and iron-laden cells). To explain these observations, we have developed a multi-compartmental geometric model of whitematter micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 47 publications
4
105
0
Order By: Relevance
“…[6] to model local exchangeinduced, u-independent frequency offsets in WM (15), as well as u-independent WM frequency shifts due to microstructure (19,20,23,34). Previous work by our group (19) and others (15,21,43) has suggested that there are exchange-related frequency offsets on the order of 0.01ppm in WM relative to GM, which at 7T corresponds to a frequency offset of %3Hz.…”
Section: Simulating Whole Brain Frequency Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] to model local exchangeinduced, u-independent frequency offsets in WM (15), as well as u-independent WM frequency shifts due to microstructure (19,20,23,34). Previous work by our group (19) and others (15,21,43) has suggested that there are exchange-related frequency offsets on the order of 0.01ppm in WM relative to GM, which at 7T corresponds to a frequency offset of %3Hz.…”
Section: Simulating Whole Brain Frequency Mapsmentioning
confidence: 99%
“…Recently, however, several research groups have described additional mechanisms that could give rise to phase contrast in GE images: (i) exchange processes (15); (ii) nuclear magnetic resonance (NMR)-invisible microstructure (16); (iii) anisotropic magnetic susceptibility (17,18). Despite an increasing effort to quantify the contributions of each of these contrast mechanisms to phase measurements (19)(20)(21)(22)(23), the effect that these contributions have on susceptibility maps, calculated using QSM methods that assume isotropic magnetic susceptibility is the only cause of phase variation, has not been characterized. Only by understanding the impact of the additional phase contrast mechanisms on susceptibility mapping can the true value of QSM and other related methods be fully appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, phase was changed iteratively until the integral under the absorption spectrum was maximized. Because models of water spectra from white matter [22][23][24] indicate that the frequency shifts between compartments is on the order of tens of Hz, a spectral bandwidth of 111 Hz was considered sufficient to resolve the water resonance. Additionally, at 9.4 T fat is ∼1380 Hz from water (3.5 ppm).…”
Section: C Data Processingmentioning
confidence: 99%
“…As a result, conventional single echoacquisitiontechniqueshavelimitedsensitivitytothesubtle variations in magnetic susceptibility due to microstructure predictedbywhitematterMRIsignalmodels.Thesemodelspredict small (on the order of Hz) but distinct changes in resonance frequency associated with white matter anatomy. [22][23][24] In addition, sensitivity to non-Lorentzian features of the water resonance is limited because the apparent phase within a voxel detected by single echo methods is an average value over all frequency components of the measured signal. This is a necessary trade-off between spectral resolution, spatial resolution, and the volume of tissue that can be imaged with acceptable run-times.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have aimed to spatially map, characterize and quantify susceptibility effects and represent them as unique intra-voxel signal compartments (Chen et al, 2013;Hernando et al, 2008;Wu et al, 2017;Xu et al, 2015). For example, a technique known as myelin water fraction (MWF) imaging has greatly benefitted from the use of mGRE-MRI.…”
Section: Decoding the Mgre-mri Signal Through Compartmentalizationmentioning
confidence: 99%